Limit Efek Stochastik untuk Thermally Assisted Magnetization Reversal: Hanin Firdausi, Utari, Budi Purnama - Hanin Firdausi, Hanin Firdausi; Utari, Utari; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Evaluation of stochastic limit for thermally assisted magnetization reversal (TAMR) discussed in this paper. This simulation is done by solving the equation Landau-Liftshitz-Gilbert (LLG) assuming nanoparticles CoPtCr perpendicular magnetic anisotropy as a memory cell storage. The magnetization direction aligning along to the external field direction of H = 2.0 kOe started when the writing temperature TW is 95.2%TC and increased steadily up to 85% when TW = 97.86% of TC. So that this condition (TW = 97.86% of TC) is regarded as the limit of stochastic for TAMR in this study. Finally, the writing temperature increase of 99.97%TC only raise thepercentage of MX in the direction of the external field H by 10%.